Serotyping, a challenging approach for Toxoplasma gondii typing - Sousa, Susana; Fernandes, Maria; Correia da Costa, José Manuel (Frontiers in Medicine, 2023)
Genotype analysis has revealed a high genetic diversity in strains of Toxoplasma gondii, isolated from a wide range of intermediate hosts and different geographic origins. Diversity is notably striking for parasites from wild hosts in South America, generally referred as non-archetypal genotypes. Those genotypes are implicated in the etiology of severe clinical disease, multivisceral toxoplasmosis, associated with high rate of mortality in immunocompetent individuals. Can we accept specific antibodies produced during T. gondii infection as biomarkers to identify infecting genotypes? Scientific evidence supports a positive response to this question; however, the genetic diversity of T. gondii genotypes organized into 16 haplogroups and collectively defined in six major clades, provides a reminder of the complexity and difficulty for the purpose. This review discusses serological approaches to genotyping T. gondii.